Update on pathogenesis and immunology of Graves’ ophthalmopathy - Larysa Krajewska-Węglewicz (Central European Journal of Immunology, 2018)
Graves’ ophthalmopathy (GO) is an inflammatory autoimmune disorder of the orbital adipose tissue and extraocular muscles, and it is associated with Graves’ disease (GD). GO is triggered by binding and activation of orbital fibroblasts by autoantibodies (TSI) direct against thyroid-stimulating hormone receptor (TSHR) and insulin-like growth factor 1 (IGF-1R), which is highly expressed within the orbit. Moreover, interaction of T cells with orbital fibroblasts that involve T-cell receptor (TCR), autoantigen, and major histocompatibility complex class II (MHC II) molecule, as well as CD40:CD154 signalling, activates p38, ERK 1/2, and JNK pathways. These processes induce fibroblast activation, proliferation, and secretion of chemokines and inflammatory cytokines to maintain inflammation within the orbit. Furthermore, increased hyaluronic acid production and fibroblast differentiation into adipocytes and myofibroblasts leads to development of GO. The elevated number of molecular factors such as PDGF, IL1-β, IL-4, IL-6, IL10, IL-8, IL-16, IL-33, HGF, ICAM-1, osteopontin, CTLA-4, and TGF-β are discussed in the paper. Some of them are key markers of disease stage. Better understanding of GO pathogenesis leads to development of new therapeutic options.